Interactive 3D courseware for Spanish language - Chan, Calvin Quok Qeith (2014)
The conventional way in language teaching and learning is using book module, teacher centered learning, and self-learning using online vocabulary. Nowadays, the method for language teaching and learning using multimedia become popular. There are several disadvantages of learning language using conventional way such as the learners have to imagine the words that they learn without feeling the situation of usage. Multimedia can allow the student to learn through cognitive strategies where steps are carefully taken to process linguistic and sociolinguistic contents. These include selecting information from incoming data, comprehending it, storing it, and retrieving it for later use. The main aim of this project is to develop an interactive 3D courseware for Spanish. 3D technology implementation for the use of education is still fairly new despite the technological advances in 3D modelling. With this courseware, learners of the Spanish language could learn the language via 3D walkthrough. The purpose of this report is to outline and describe the methods and development process of the aforementioned project.